Gender Equity in the Marketing Academy: From Performative to Institutional Allyship. Issue 3 (August 2022) - Dobele, Angela R.; Ferguson, Shelagh; Hartman, Anna E.; Schuster, Lisa
The fair treatment of women in the workplace, where they experience both opportunities and constraints, has been on and off higher education agendas for decades. Yet, institutionalised gendered constraints still shape the careers of female academics, including those in the marketing academy, resulting in disrupted or obstacle-heavy career journeys and the underrepresentation of women in senior positions. Furthermore, progress towards gender equity is hampered by institutional resistance to change, favouring performative rather than genuine and transformational institutional allyship. We draw upon personal experiences, recollections and anecdotes garnered over the years – synthesised with literature – to examine systemic gendered constraints within our collective career span. We propose institutional allyship as the intentional efforts needed by the marketing academy to address systemic and structural gender inequities and achieve second-order change by integrating gender equity outcomes throughout organisational decision-making. Specifically, we suggest nominated actions within a Gender Equity and Inclusion Charter for the Australian and New Zealand Marketing Academy (ANZMAC) and its member universities as a first step.